Komunikasi Data Reporting System Pada Gas Chromatography Berbasis LabView Melalui Wireless - Taufik Hidayat Soi (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2020)
ABSTRACT : Gas Chromatography Gas Chromatography is used in various industrial fields, especially in quality control. Each brand has a gas chromatography special software provided by manufacturing. And the software can only be used in accordance with the rules. Targets the analysis results will be printed according to the format in the software. However, in the development of software today is a lot of software that can be combined or developed with software engineering, such as LabView. LabView can we develop the software - software that already exist today. Labview can simplify and speed the operator in the printing, selecting, and report the results. Efficient in the can by using LabView is more than 50%.